Co-infection with two novel mycoviruses affects the biocontrol activity of Trichoderma polysporum - Jeesun Chun; Hae-Ryeong Yoon; Sei-Jin Lee; Dae-Hyuk Kim (Biological Control)
This study reports the whole genome sequence of two double-stranded RNA viruses (mycoviruses) that co-infected an isolate of Trichoderma polysporum NFCF205 and the interactions between fungus and virus. Based on genome size, organization, sequence similarity, and phylogenic analysis, one of these is best characterized as a new member of the proposed family “Fusagraviridae”, and accordingly suggest that it be referred to as Trichoderma polysporum fusagravirus 1 (TpFGV1). The other is best classified as a new strain of the genus Alphapartitivirus in the family Partitiviridae, and should be designated Trichoderma polysporum partitivirus 1 from T. polysporum NFCF205 (TpPV1). By single spore isolation, virus-free or singly-infected isogenic strains were obtained and compared to determine the biological functions of the viruses. The colony morphology of the co-infected parental strain showed the characteristic spiraled hairy and fluffy mycelia, while both the singly-infected and virus-free strain rarely showed the conspicuous aerial mycelia. The growth rate of the co-infected strain was slightly, but nevertheless statistically significantly, higher on PDA. Interestingly, conidia production was observed to have significantly increased in the co-infected strain while no difference was seen in the others. Growth inhibition measured by dual-culturing with Rhizoctonia solani revealed a significant difference between the co-infected strain and a TpPV1-infected strain. However, the secreted soluble compounds in the co-infected strain showed the least antimicrobial activity. Moreover, antimicrobial activities via volatile organic compounds (VOCs), which signify strong biocontrol activity by Trichoderma spp., was the lowest in the co-infected strain. The profiles and amount of representative VOCs in the assessed strains, as measured by gas chromatography-mass spectrometry (GC/MS/MS), were affected by virus-infection. Virus infection affected colony morphology, conidia production, and biocontrol activities of T. polysporum. Most interestingly, virus-virus interaction was observed and measured in the co-infected strain, as their symptoms differed from those of the singly-infected strains.